ENHANCING LOCAL TOURISM THROUGH COMPARATIVE ANALYSIS AND DIGITAL INNOVATION: AN ANDROID-BASED APPROACH - Gupta, Shubham; Verma, Raj; Narayan, Vipul (International Journal of Research -GRANTHAALAYAH, 2025)
Tourism significantly contributes to local economies, yet many destinations struggle to provide tourists with accurate, accessible information. Existing apps often lack integration and usability, leading to fragmented experiences. This paper compares existing tourism apps and introduces an Android-based mobile application that integrates features like language translation, a chatbot for real-time assistance, and GPS-enabled navigation. By addressing gaps identified in the comparison, the app promotes lesser-known attractions, provides real-time updates on events, and enhances user engagement and cultural appreciation. The findings demonstrate how digital innovation, combined with insights from comparative analysis, can improve tourist experiences, support local businesses, and create a connected tourism network.